Investigate the use of electrostatics in fabricating 3D objects using additive manufacturing technology - Foo, Ting Wei (2015)
3-Dimensional (3D) printing has been making waves in the manufacturing sector, winning the popularity of many different users, from specialized industries to the everyday consumer. The additive technology of 3D printing causes it to bypass restrictions previously imposed by current conventional manufacturing technology. While 3D printing is poised to overtake current traditional manufacturing methodologies, there are still several limitations holding it back. One such limitation is the speed of 3D printing technology. Most of the additive technology currently used prints each layer by individual points of the image, which can be rather slow. In this paper, the focus is on the development of electrostatics to be used for 3D printing. Utilizing electrostatics in 3D printing presents a great potential to vastly improve its speed. This is because layers are printed whole instead of individual points. A laser printer will be used as the subject of the experiment. Through its modification, the paper aims to understand how electrostatics can be used to develop a new way of 3D printing.